Intermediate-Term Outcomes Following Operative and Nonoperative Management of Midshaft Clavicle Fractures in Children and Adolescents: Internal Fixation May Improve Outcomes. Issue 1 (January 2021) - Swarup, Ishaan; Maheshwer, Bhargavi; Orr, Steven; Kehoe, Clare; Zhang, Yi; Dodwell, Emily
Abstract : Background: Although multiple prospective comparative studies exist for adults with midshaft clavicle fractures, few comparative studies exist in older children and adolescents. This study compares intermediate-term functional, pain, radiographic, and complication outcomes in children and adolescents with midshaft clavicle fractures treated operatively or nonoperatively. Methods: Children and adolescents who were 10 to 18 years of age with midshaft clavicle fractures treated from 2006 to 2017 were identified through electronic picture archiving and communication system (PACS) radiographic and chart review. Closed injuries with a minimum of 1 year from the time of the injury were included. Patients completed patient-reported outcome measures and a focused questionnaire. The primary outcome was the abbreviated Disabilities of the Arm, Shoulder and Hand Questionnaire (QuickDASH) score; the secondary outcomes included the University of California Los Angeles (UCLA) Activity Scale, Patient-Reported Outcomes Measurement Information System (PROMIS) Pain Interference (PI) and PROMIS Physical Function (PF) Upper Extremity (UE), Hospital for Special Surgery Pediatric Functional Activity Brief Scale (HSS Pedi-FABS), Numeric Rating Scale (NRS) for Pain, and rates of implant removal, nonunion, and refracture. Univariate comparisons between the operatively treated group and the nonoperatively treated group were performed. Results: In this study, 302 patients were identified; of these, 79 patients (43 operatively treated and 36 nonoperatively treated) or their parent or legal guardian consented and the patients completed the study protocol. The mean age (and standard deviation) at the time of the injury was 16.0 ± 1.7 years for the operatively treated group and 13.5 ± 1.8 years for the nonoperatively treated group (p < 0.001). The median follow-up was 3.8 years. The patient-reported outcome scores were similar (p > 0.05 for all comparisons) between the operatively treated group and the nonoperatively treated group, even for patients at or near skeletal maturity and those with shortening of ≥15 mm or ≥100% translation. There were no nonunions. The refracture rate was 5% (2 of 43) for the operatively treated group and 3% (1 of 36) for the nonoperatively treated group (p = 1.00). There were 19% (8 of 43) who underwent implant removal. Responders were similar to nonresponders, other than female patients (p < 0.001) and surgically treated patients (p = 0.049) being more likely to respond. Conclusions: In the subset of this cohort who responded and completed the study, both operatively and nonoperatively treated patients had excellent functional and pain outcomes, similar refracture rates, and no nonunions. Even in widely displaced and translated fractures, and in those at or near skeletal maturity, outcomes were similar. Operative management should potentially be reserved for special circumstances. A prospective comparative study of older adolescents (female patients who are 14 to 18 years of age and male patients who are 16 to 20 years of age) with displaced midshaft clavicle fractures is warranted. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.